Sunset Pura Ulun Bali Sebagai Inspirasi Dan Aplikasi Tata Rias Face Painting - Noverainsy Millenia Suhandi (JURNAL RUPA, 2022)
Face painting is a kind of art that use a face to be the media; it is included in the art of makeup because it changes the face of some people to get the purpose of art. For now, face painting has grown into makeup and makes a face look more glamorous in any event, such as a Halloween party, carnival, UV glow painting, and fashion art wear. Many artists or influencers in cosmetology apply new techniques to get unique makeup. One of them is the grading color technique, a color transition gradually, combining some elements of change with exciting unity. Beautiful view of nature in Dewata Bali Island, exactly the sunset at Pura Ulun Danu Bratan has no doubt anymore. Hill views distributed the typical Bali architecture of Pura, and rivers have become a source of face painting makeup. This research uses the Project Based-Learning method to produce a product in the form of face painting by applying color gradation techniques; the technique is quite simple and makes the makeup look more natural. This study’s results can motivate artists to develop face-painting makeup ideas.